Extracorporeal life support in the multidisciplinary management of cardiogenic shock complicating acute myocardial infarction. Issue 3 (29th April 2019) - Pozzi, Matteo; Flagiello, Michele; Armoiry, Xavier; Generali, Tommaso; Adamou Nouhou, Kaled; Koffel, Catherine; Schweizer, Remi; Fellahi, Jean Luc; Cuenin, Leo; Cellier, Guillaume; Green, Lisa; Derimay, Francois; et al.
Abstract: Objectives: To analyze the results of extracorporeal life support (ECLS) for cardiogenic shock complicating acute myocardial infarction (AMI) in a single‐center experience. Background: Cardiogenic shock is still a leading cause of death for AMI. Conventional management carries mortality rates exceeding 50%. ECLS may be considered as a bridge to decision in the setting of AMI complicated by cardiogenic shock not responsive to standard management. Methods: We performed an observational analysis of our local database. The primary end‐point was survival to hospital discharge. All variables were compared between survivors and nonsurvivors. Results: Between January 2007 and December 2017, 56 patients were supported for cardiogenic shock complicating AMI. The mean age was 56.7 years and 89.3% were males. Baseline characteristics were comparable between both groups. Of the 50 primary percutaneous coronary interventions that were attempted, 44 (88.0%) were successful. Twenty‐three (41.1%) patients died during ECLS support. The complications' rate during ECLS support was comparable between both groups. Twenty‐eight (50%) patients were successfully weaned from ECLS after a mean support of 8.7 days. Eight (14.3%) patients eventually died after weaning before hospital discharge. Five (8.9%) patients could not be weaned from ECLS and were switched to a long‐term mechanical circulatory support. Overall survival to hospital discharge was 41.1% ( n = 23). Eighteen (32.1%) patients were alive after a mean follow‐up of 38.0 ± 29.9 (range, 4.2–95.4) months. Conclusions: ECLS should be considered as a therapeutic solution in the management of AMI‐related cardiogenic shock with a satisfactory short‐ and long‐term survival.